Leveraging the role of computer vision in agriculture applications - Gakhar, Shalini; Patwar, Shelly; Sharma, Sheetal; Tiwari, K. C. (2023)
The International Rice Research Institute (IRRI) conducted a one-day workshop on “Leveraging the Role of Computer Vision in Agriculture Applications” as part of the CGIAR Initiative on Digital Innovation Initiative (DI). The workshop was organized at Delhi Technological University (DTU) on 20th November 2023. It was a joint effort by CGIAR's IRRI with DTU, New Delhi, and was meant for research scholars, and engineering students working in the field of Digital Agriculture. Sessions on the latest technologies used in Digital Agriculture were conducted during the workshops. A total of 36 participants (12 Females and 24 Males) participated and benefited from the workshop.